Налоговое право России: курс лекций / И. И. Кучеров - Кучеров Илья Ильич (Библиотека "ЮрИнфоР", 2006)
Экземпляры: аб. (2008) / Инвентарный номер: 51675 / Цена: / Сис.шифр: 67.402 / Авт.знак: К 95 / ГРНТИ: 10.21.63 / ББК: 67.402